ASYMPTOMATIC BACTERIURIA AND PREGNANCY - Matrizaeva Kurbonbika Madrimovna; Yusupova Mehribon Atakhanovna (Innovate Conferences, 2025)
Microbial colonization of the urinary tract and, accordingly, the presence of bacteria in the urine without clinical manifestations of urinary tract infection (UTI) is defined as asymptomatic bacteriuria (AB). In the female population, BD is common, but its prevalence varies widely depending on geographic region, even within the same country, gender, age, sexual activity, functional and structural disorders of the urinary system, associated conditions and diseases. Among the healthy female population, the prevalence of BD increases with age – from 1% among schoolgirls to 16% or more among women 70 years and older. In young women, it is closely associated with sexual activity (in 5% of healthy premenopausal married women, but only 0.7% of nuns). In non-pregnant women, the incidence of BD is approximately 5%; in pregnant women, it ranges from 2% to 10% or more depending on socioeconomic status and a history of previous UTIs. It typically reflects colonization of the periurethral region by microorganisms prior to pregnancy. The prevalence of significant bacteriuria, determined by a single urinary catheterization at delivery, was 2% in pregnant women of middle socioeconomic status compared with 6.5% in pregnant women of low socioeconomic status.
Keywords: Urinary tract infection, asymptomatic bacteriuria, bacteriuria, pregnancy.